Parametric analysis of single boost converter for energy harvester - Che Mustapha, Nurul Arfah; Alam, A. H. M. Zahirul; Khan, Sheroz; Azman, Amelia Wong (2015)
This paper presents a conventional DC-DC boost converter for low and wide voltage supply range, suitable for energy harvesting purpose. The output voltage can be increased by controlling the transistor switching frequency, duty cycle,inductance, load capacitor, rise, and fall time. Both computer simulation and experiment results are performed in details. Experiment results have shown an error less than 6 % with the simulation. A linear trend of output voltage in the range of 4 V to 49 V is successfully converted from 100 mV to 1.5 V input voltage using low switching frequency of 2 kHz. The circuit parameter for this voltage range are L = 100 μH, D = 50 %, tr = tf = 2.9 μs considering CL = 10 μF, and RL = 10 k